Pragmatic paradigm in information science research - Borges, Leonor Calvão; Revez, Jorge (Qualitative and Quantitative Methods in Libraries; Vol 8 No 2 (2019): June 2019 Issue, 2019)
In social science research, Pragmatic Paradigm was proposed as a philosophical basis for mixed methods research, supporting a third option to qualitative and quantitative methods dichotomy. The paradigm wars between these approaches often encouraged the application of rigid methodological frameworks and the temptation of creating ‘one size fits all’ epistemological solutions. To overcome these issues, pragmatism focused on obtaining the necessary data to answering research questions, rejecting pre-established methods design. Several studies performed analysis of mixed methods research presence in information science but those which mentions the pragmatic paradigm are poorly known. In this paper, we explore the rationale and the foundations of the pragmatic paradigm and its applications in information science research. Using a recent literature review ( Web of Science and Scopus ), the main objective is to understand pragmatic paradigm presence in information science literature, understanding if mixed methods researchers and others refer pragmatism as their philosophical basis. The analysis shows that information science research is not aware of the pragmatic paradigm as a methodological foundation neither recognize it as a basis for mixed methods research. Nevertheless, knowledge acquisition about information science field is still enriched through the study and observation of this paradigm choice.